2019
DOI: 10.20473/amnt.v3i3.2019.171-175
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Riwayat Pemberian Makanan Pendamping ASI (MP-ASI) dengan Persepsi Perilaku Picky Eater pada Anak Usia 12-36 Bulan (Studi di Wilayah Kerja Sidotopo Surabaya)

Abstract: Background : Pre-school age children often have picky eater behavior. Perception of picky eater usually describes as the strong preference of children for food, inadequate of dietary diversity, restrain of certain food groups and won’t try new food. One of factors that causes this behavior is history of complementary feeding.Objectives: This study purposes was to analyze correlation between history of complementary feeding and perception of picky eater behavior among children age 12-36 month oldMethods: This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…That's why both boy and girl can show fussy eating habits. Ariyanti (2023) found that food acceptance is a significant factor in children's behavior regarding picky eating. Many things influence how we react to food, including how we were raised and how we consume food as we age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That's why both boy and girl can show fussy eating habits. Ariyanti (2023) found that food acceptance is a significant factor in children's behavior regarding picky eating. Many things influence how we react to food, including how we were raised and how we consume food as we age.…”
Section: Resultsmentioning
confidence: 99%
“…Children at this age often show a natural reluctance to try unfamiliar foods. Children are more likely than adults to develop difficult or fussy eating habits because their sense of taste is more developed 10 . Research and theory show that picky eating is a common occurrence among preschool children.…”
Section: Resultsmentioning
confidence: 99%
“…Perilaku picky eater banyak terjadi pada anak usia prasekolah (Cahyani, 2019). Prevalensi picky eater terjadi pada anak usia 24-35 bulan sebesar 36 % lebih tinggi dibandingkan pada usia 6-11 bulan sebesar 12 % di negara Cina (Li et al, 2017).…”
unclassified
“…Jika terlalu cepat yang mana motoric bayi belum siap akan beresiko tersedak, pencernaan bayi yang belum siap dapat menimbulkan gangguan pada pencernaan dan juga dapat menjadi faktor resiko alergi, eksim dan obesitas (Sariy, Simanjuntak, & Suryani, 2018). Sedangkan jika terlalu lambat MP-ASI diberikan kemungkinan yang dapat muncul seperti gangguan pertumbuhan akibat asupan nutrisi dari ASI eksklusif tidak mencukupi kebutuhan bayi, dan akan timbul bayi dengan picky eater atau penolakan terhadap MP-ASI akibat anak tidak terbiasa (Cahyani, 2019). Seiring dengan pertumbuhan bayi, maka akan bertambah pula kebutuhan gizinya.…”
unclassified